Left-right asymmetry in the level of active Nodal protein produced in the node is translated into left-right asymmetry in the lateral plate of mouse embryos - Kawasumi, Aiko (2018)
Left-right (L-R) asymmetry in the mouse embryo is generated in the node and is dependent on cilia-driven fluid flow, but how the initial asymmetry is transmitted from the node to the lateral plate has remained unknown. We have now identified a transcriptional enhancer (ANE) in the human LEFTY1 gene that exhibits marked L>R asymmetric activity in perinodal cells of the mouse embryo. Dissection of ANE revealed that it is activated in the perinodal cells on the left side by Nodal signaling, suggesting that Nodal activity in the node is asymmetric at a time when Nodal expression is symmetric. Phosphorylated Smad2/3 (pSmad2) indeed manifested an L-R asymmetric distribution at the node, being detected in perinodal cells preferentially on the left side. This asymmetry in pSmad2 distribution was found to be generated not by unidirectional transport of Nodal but rather as a result of L<R asymmetric expression of the Nodal antagonist Cerl2. For various mutant embryos examined, the asymmetry in pSmad2 distribution among the perinodal cells closely matched that in lateral plate mesoderm (LPM). However, autocrine-paracrine Nodal signaling in perinodal cells is dispensable for L-R patterning of LPM, given that its inhibition by expression of dominant negative forms of Smad3 or ALK4 was still associated with normal (left-sided) Nodal expression in LPM. Our results suggest that LPM is the direct target of Nodal secreted by the perinodal cells, and that an L>R distribution of active Nodal in the node is translated into the asymmetry in LPM. (C) 2011 Elsevier Inc. All rights reserved.